Hubungan Antara Asupan Asam Folat Dan Vitamin B12 Dengan Status Depresi Pada Pasien Cedera Tulang Belakang Di Rumah Sakit Ortopedi Prof. DR. R. Soeharso Surakarta - Wulandari, Elsa, Siti Zulaekah, A, M.Si, Setia Asyanti, S.Psi, M.Psi (2015)
Introduction: Depression is commonly seen in patients with spinal cord injuries because it takes care and a long recovery. In the state of depression, spinal cord injury patients do not pay attention to diet such as loss of appetite resulting in the intake of folic acid and vitamin B12 decreases. Folic Acid and Vitamin B12 protects arteries by converting homocysteine to cysteine. High homocysteine levels cause disruption kognotif and can increase the severity of depression. Objective: The aim of study was to determine the relationship between the intake of folic acid and vitamin B12 with depression status in patients with spinal cord injuries in the RSO.Prof.DR.R.Soeharso Surakarta. Methods: This was an observational study with cross sectional approach. The sample size of 35 people according to the inclusion criteria. Sampling by means of consecutive sampling. Adequate intake level data retrieval folic acid and Vitamin B12 do form a 24-hour food recall for four days in the morning, afternoon and evening. Depression status data obtained by measuring the level of depression with a questionnaire Beck Depression Inventory (BDI). The statistical test used Spearman Rank.. Results: The results showed 88.6% of the subjects had less folic acid and vitamin B12 intake, 11,4% had intake of folic acid and vitamin B12 enough. Most subjects 31.4% samples experienced mild depression, while 17.1% had moderate depression, 5.7% severe depression, meanwhile 45.7% had no depression. Based on the results of Spearman Rank p-value of relationship between folate with depression status and there was no association between vitamin B12 with depression status. Conclusion: To sum up there were any relationship between the intake of folic acid with depression status (p = 0.022) and there was no association between the intake of vitamin B12 with depression status (p = 0.201).